2023
DOI: 10.3390/vetsci10060393
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Tenebrio molitor Larvae Reared with Different Substrates as Feed Ingredients in Growing Pigs

Abstract: The procurement of adequate feed resources is one of the most important challenges for the animal industry worldwide. While the need for feeds rich in protein is constantly increasing, their production cannot readily keep up. Consequently, to overcome this challenge in a sustainable way, it is necessary to identify and develop new feeding strategies and feed ingredients, such as insect meals. In the present study, Tenebrio molitor larvae that were reared on two different substrates (standard and enriched with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…It appears that there is a relationship between the content of dietary phenols in the meat and its resistance to oxidative damage. These observations are in agreement with previous studies, which reported that the use of T. molitor in monogastric animal diets can improve the oxidative stability of the meat [ 47 , 82 ]. Xu et al reported that incorporating chitosan into the diets of weaned piglets led to an increase in total antioxidant capacity along with a reduction in the levels of MDA and cortisol in serum [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It appears that there is a relationship between the content of dietary phenols in the meat and its resistance to oxidative damage. These observations are in agreement with previous studies, which reported that the use of T. molitor in monogastric animal diets can improve the oxidative stability of the meat [ 47 , 82 ]. Xu et al reported that incorporating chitosan into the diets of weaned piglets led to an increase in total antioxidant capacity along with a reduction in the levels of MDA and cortisol in serum [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the fatty acid composition of T. molitor larvae and meals can be improved through modification of the rearing substrate [ 102 ]. Our results are in agreement with recent studies, which also reported a decrease in saturated fatty acids (SFA) and an increase in polyunsaturated and omega-3 fatty acids in the produced meat of growing pigs when H. illucens , T. molitor , and A. diaperinus larvae meals were added in the diets [ 82 , 103 , 104 , 105 ]. In contrast, there is limited research on the effect of chitosan supplementation on pork meat fatty acids.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The yellow mealworm, Tenebrio molitor L. (Coleoptera: Tenebrionidae), has been extensively studied for its potential to be utilized as a nutrient source for farmed fish (Iaconisi et al 2017 ; Jeong et al 2020 ), poultry (Khan et al 2018 ; Mastoraki et al 2020 ; Vasilopoulos et al 2023 ), pigs (Jin et al 2016 ; Zacharis et al 2023 ) and other livestock animals. In 2017, T. molitor was listed among the approved insect species as aquafeed ingredients (EC 2017 ).…”
Section: Introductionmentioning
confidence: 99%